Confluent and Reticulated Papillomatosis of Gougerot-Carteaud on Black Skin: Two Observations - Kouadio Celestin Ahogo; Patrice Ildevert Gbery; Vagamon Bamba; Yao Isidore Kouassi; Elidje Joseph Ecra; Kouame Alesandre Kouassi; Ange Sylvain Allou (Case Reports in Dermatological Medicine)
Confluent and reticulated papillomatosis of Goujerot-Carteaud is a rare and benign skin disease characterized by flat papules taking a reticulated appearance. It is a skin disease of unknown etiology and nosology that is always discussed. This disease preferentially involves the chest and interscapular regions. It is a condition probably underdiagnosed in black skin because it generally simulates a pigmented tinea versicolor. This pathology withstands antifungal treatment but has a particular sensitivity to cyclines thus constituting a distinguishing criterion, useful for diagnosis which should be evoked in front of these reticulated confluent papules.